2020
DOI: 10.31234/osf.io/u5yts
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Political psychology in the digital (mis)information age: A model of news belief and sharing

Abstract: The spread of misinformation, including “fake news,” disinformation, and conspiracy theories, represents a serious threat to society, as it has the potential to alter beliefs, behavior, and policy. Research is beginning to disentangle how and why misinformation is spread and identify processes that contribute to this social problem. Here, we review the social & political psychology that underlies the dissemination of misinformation and highlight strategies that might be effective in mitigating this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Here we showed that dyads will accept false feedback about their past choices and that doing so affects their later choices. This result extends the phenomenon of choice-induced preference change to groups, and reminds us that in this hyper-connected social media age to be ever vigilant of the accuracy of the group feedback that we receive (Allington, Duffy, Wessely, Dhavan, & Rubin, 2020;Van Bavel et al, 2020). quality of multiattribute judgments.…”
Section: Resultssupporting
confidence: 70%
“…Here we showed that dyads will accept false feedback about their past choices and that doing so affects their later choices. This result extends the phenomenon of choice-induced preference change to groups, and reminds us that in this hyper-connected social media age to be ever vigilant of the accuracy of the group feedback that we receive (Allington, Duffy, Wessely, Dhavan, & Rubin, 2020;Van Bavel et al, 2020). quality of multiattribute judgments.…”
Section: Resultssupporting
confidence: 70%
“…Social media sharing often reflects a desire to maintain a positive self-presentation (17,29). This can lead to different outcomes depending on the context, social norms, and design features of one's online network (59), since strategies to maintain a positive self-image may differ by context (26,60). While many studies find a negativity bias in online sharing (19,52), there are some contexts where positive content is shared more often.…”
Section: Discussionmentioning
confidence: 99%
“…While political views have been linked to receptivity to bullshit and engagement with false news (findings we replicate in our data, see Footnote 11), this does not seem to play any role in explaining our findings regarding deprivation curiosity. While deprivation curiosity explains only a small part of the variance in people's susceptibility to disinformation, and other factors likely play a bigger role (e.g., Van Bavel, Harris, Pärnamets, Rathje, Doell, & Tucker, 2021), it is remarkable that curiosity, which is usually portrayed as a virtue, can have this negative aspect to it.…”
Section: Discussionmentioning
confidence: 99%